Isotopologue-selective laser cooling of molecules - Felix Kogel; Tatsam Garg; Marian Rockenhäuser; Sebastián A Morales-Ramírez; Tim Langen (New Journal of Physics)
Direct laser cooling of molecules has made significant progress in recent years. However, the selective cooling and manipulation of generic molecular samples based on their isotopic composition, which is ubiquitous in atomic laser cooling, has not yet been achieved. Here, we demonstrate such isotopologue-selective laser cooling and near-arbitrary control over the isotopic composition of a molecular beam, using barium monofluoride (BaF) as an example. The manipulation of the rare and previously uncooled ${} ^{136}BaF$ is achieved in the presence of several isotopologues of significantly higher natural abundance. Our results enable intense molecular beams, high fidelity detection and manipulation of select low-abundance isotopologues or isotopic mixtures. Such beams are a first step towards isotopologue-selective molecular trapping and will be useful for applications in trace gas analysis, cold collisions and precision tests of fundamental symmetries.